A three-stage DEA analysis and a black-box approach of the performance of commercial banks in Ghana : an evaluation of efficiency, competition and profitability - Oku, Barbara Naa Ayeley; Stellenbosch University. Faculty of Economic and Management Sciences. University of Stellenbosch Business School. (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.